Lawsuit Regarding Sale and Purchase (Case Study Against PT Antam and Budi Said Crazy Rich Surabaya) - Lo, Edmund; Lie, Gunardi; Syailendra Putra, Moody Rizqy (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Buying and selling is an activity that is carried out by many people, but in the transaction process it must be carried out with the consent of both parties, so that the sale and purchase is only valid according to law. This can also be interpreted in the buying and selling of gold between Budi Said as the buyer and also PT Antam as the gold provider. However, the problem was that when PT Antam employees sent gold to Budi Said, it was explained that the gold received was not in accordance with the weight agreed upon at the beginning. This made Budi Said file a lawsuit against PT Antam for the discrepancy between the gold he received and the amount agreed upon and promised together. The lawsuit was accepted by PT Antam for violating the law, even though clarification should have been made and employees were also responsible. If we look at it from the other side, then when Budi bought gold from PT Antam which he promised, namely through Eksi who was one of PT Antam's employees, this was explained by PT Antam that they had never sold gold below the price set in the company profile. , but in fact the agreement made by Eksi with Budi was far below the normal price or that explained by PT Antam.